The potential role of boswellic acids in cancer prevention and treatment - Roy, N.; Deka, A.; Bordoloi, D.; Mishra, S.; Kumar, Alan Prem; Sethi, G.; Kunnumakkara, A. (Elsevier, 2016)
© 2016 Elsevier Ireland Ltd. Despite the extensive research carried out in the field of cancer therapeutics, cancer is one of the most dreadful diseases in the world with no definitive treatment to date. The key attributes responsible for this are the various limiting factors associated with conventional chemotherapeutics that primarily include adverse side-effects and development of chemoresistance. Hence, there is an utter need to find compounds that are highly safe and efficacious for the prevention and treatment of cancer. Boswellic acid, a group of pentacyclic compounds, seems to be promising enough due to its inherent anti-cancerous properties. Considering this perspective, the present review highlights the established studies related to the anti-cancer potential of boswellic acid against different cancer types. The molecular mechanisms underlying the targets of boswellic acid that are accountable for its potent anti-cancer effect are also discussed. Overall, this review projects the pieces of evidence that reveal the potential of boswellic acid as a suitable candidate that can be appropriately developed and designed into a promising anti-cancer drug.